Process chains for high-precision components with micro-scale features. Issue 2 (2016) - Uhlmann, E.; Mullany, B.; Biermann, D.; Rajurkar, K.P.; Hausotte, T.; Brinksmeier, E.
Abstract: This keynote paper addresses the manufacturing of high-precision components with micro-scale features, and the associated process chain considerations. Three workpiece classifications as well as a micro-production process chain (MPPC) model are defined. A review of capabilities and advances in micro-manufacturing technologies, metrology, and equipment demonstrates increased versatility across varied applications, while also highlighting limitations. Challenges in the development of process chains are presented using results of the MPPC program of the Collaborative Working Group on Micro-Production Engineering. Finally, a guide for machining high-precision components with micro-scale features in process chains is given with respect to machine tools, tools, technology and environmental conditions.